Latino politics en ciencia política : the search for Latino identity and racial consciousness - Affigne, Tony; Hu-DeHart, Evelyn; Orr, Marion, 1962- (New York University Press, 2014)
"More than 53 million Latinos now constitute the largest, fastest-growing, and most diverse minority group in the United States, and the nation's political future may well be shaped by Latinos' continuing political incorporation. In the 2012 election, Latinos proved to be a critical voting bloc in both Presidential and Congressional races; this demographic will only become more important in future American elections. Using new evidence from the largest-ever scientific survey addressed exclusively to Latino/Hispanic respondents, Latino Politics en Ciencia Politica explores political diversity within the Latino community, considering how intra-community differences influence political behavior and policy preferences. The editors and contributors, all noted scholars of race and politics, examine key issues of Latino politics in the contemporary United States: Latino/a identities (latinidad), transnationalism, acculturation, political community, and racial consciousness. The book contextualizes today's research within the history of Latino political studies, from the field's beginnings to the present, explaining how systematic analysis of Latino political behavior has over time become integral to the study of political science. Latino Politics en Ciencia Politica is thus an ideal text for learning both the state of the field today, and key dimensions of Latino political attitudes"--